Energy centered management : a guide to reducing energy copnsumption and cost - Howell, Marvin T., 1936- (The Fairmont Press, Taylor & Francis, 2015)
"This book provides any organization or company a guide to use in planning, developing, and implementing an energy reduction and management program. It is specially designed to achieve energy reduction deployment from top management to all employees and on site contractors. Energy reduction deployment (ERD) can be implemented by itself and render significant savings; however, for even greater savings, this book will show how to implement energy centered management systems (ECMS) which can be in congruence with ISO 50001. This book assists in the hunt for energy waste and is designed to thoroughly cover ECMS plus addressing what additions are necessary to have ECMS conform to ISO 50001 Energy Management Systesm (EnMS). ECMS includes picking low hanging fruit, energy efficiency and energy conservation measures. It provides the checklist and information on how to perform an internal audit or self-inspection and discusses how to create an energy awareness organization culture"--Back cover
Keywords: Energy conservation.; elektronické knihy; electronic books